Coronavirus Disease-2019 Survival in Mexico: A Cohort Study on the Interaction of the Associated Factors - Márquez-González, Horacio; Méndez-Galván, Jorge F.; Reyes-López, Alfonso; Klünder-Klünder, Miguel; Jiménez-Juárez, Rodolfo; Garduño-Espinosa, Juan; Solórzano-Santos, Fortino (Frontiers in Public Health, 2021)
The pandemic caused by the new coronavirus Severe Acute Respiratory Syndrome Coronavirus-2 (SARS-CoV-2) is currently affecting more than 200 countries. The most lethal clinical presentation is respiratory insufficiency, requiring attention in intensive care units (ICU). The most susceptible people are over 60 years old with comorbidities. The health systems organization may represent a transcendental role in survival. Objective: To analyze the correlation of sociodemographic factors, comorbidities and health system organization variables with survival in cases infected by SARS-CoV-2 during the first seven months of the pandemic in Mexico. Methods: The cohort study was performed in a health system public basis from March 1st to September 30th, 2020. The included subjects were positive for the SARS-CoV-2 test, and the target variable was mortality in 60 days. The risk variables studied were: age, sex, geographic distribution, comorbidities, health system, hospitalization and access to ICU. Bivariate statistics (X2 test), calculation of fatality rates, survival analyses and adjustment of confusing variables with Cox proportional-hazards were performed. Results: A total of 753,090 subjects were analyzed, of which the 52% were men. There were 78,492 deaths (10.3% of general fatality and 43% inpatient). The variables associated with a higher risk of hospital mortality were age (from 60 years onwards), care in public sectors, geographic areas with higher numbers of infection and endotracheal intubation without management in the ICU. Conclusions: The variables associated with a lower survival in cases affected by SARS-CoV-2 were age, comorbidities and respiratory insufficiency (with endotracheal intubation without care in the ICU). Additionally, an interaction was observed between the geographic location and health sector where they were treated.